DNA Logic Circuits for Multiple Tumor Cells Identification Using Intracellular MicroRNA Molecular Bispecific Recognition. Issue 21 (5th September 2021) - Yang, Qiqi; Yang, Fan; Dai, Wenhao; Meng, Xiangdan; Wei, Wei; Cheng, Yaru; Dong, Jinhong; Lu, Huiting; Dong, Haifeng
Abstract: The aberrant expression level of intracellular microRNAs (miRNAs) holds great promise for differentiating cell types at the molecular level. However, cell subtype discrimination based on a single miRNA molecular level is not sufficient and reliable. Herein, multiple identifiable and reporting modules are integrated into a single DNA circuit for multiple cancer cell subtypes identification based on miRNAs bispecific recognition. The DNA three‐dimensional (3D) logic gate nano‐hexahedron framework extends three recognition modules and three reporting modules to form three "AND" logic gates. Each Boolean operator "AND" returns an "ON" signal in the presence of bispecific miRNAs, simultaneously enabling three types of cell subtype identification. It not only enables the discrimination of cancer cells A549 and MCF‐7 from normal cells NHDF but also successfully distinguishes different types of cancer cells. The bispecific intracellular miRNA controllable DNA circuit, with low signal‐to‐noise ratio, easily extends to various cell type discrimination by adjusting the miRNA species, provides huge opportunities for accurately differentiating multiple cell types at the molecular level. Abstract : Cellular subtype recognition based on the level of individual microRNA (miRNA) molecules is inadequate and unreliable. Herein, a nanohexahedral framework is modified to form "AND" logic gates. It can be efficiently activated by bispecific miRNAs and enables the simultaneous detection of three miRNAs. The results show that this system can distinguish cancer cells from normal cells but also different cancer cell types.